The First Metric: The WE Index, Responsiveness, and Cultural Scripts - Bahtiar, Hikmanisa; Muhammad Kholidinna Qasabandiyah (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
"First love" is often understood as the earliest relationship, but evidence from psycholinguistics, interpersonal communication, and autobiographical memory suggests that it is more accurately viewed as a narrative-cognitive status. This brief article introduces a minimal measurement framework for assessing this status through three indicators: the WE Index (the proportion of "we/us" pronouns relative to personal pronouns plus love labels/metaphors), Perceived Responsiveness, and Age-Event Compatibility as a proxy for cultural scripts. Relying on a structured narrative review of >100 studies, we map a process model of WE →Responsiveness → Event Centrality → First Love Labeling, with emotional intensity and age–event fit as drivers/moderators. The synthesis reveals consistent patterns: Higher KITA indices correlate with higher responsiveness; responsiveness supports shared reminiscing and increases centrality; centrality predicts “first love” labeling, particularly when age-event expectations are met. The researchers present a quick operationalization (5-10minute speech sample, 3-6 item responsiveness scale, 1-2 item fit check, and brief centrality measure) that is ready for replication. Conclusion: this framework summarizes complex literature into a clear, measurable, and testable starter kit, while providing practical contributions to relational assessment and education.